1991
DOI: 10.1002/bjs.1800780216
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after emergency surgery for cancer of the large intestine

Abstract: The data for 77 patients with colorectal cancer who underwent emergency surgery for acute intestinal obstruction (57 patients) or perforation (20 patients) within 24 h of admission were evaluated. The patients were older and had more advanced disease than patients undergoing elective surgery for colorectal cancer. Emergency surgery for carcinoma of the right colon consisted of primary resection in 95 per cent of cases and was followed by a 28 per cent mortality rate. Perforated tumours of the left colon and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
70
4
11

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(99 citation statements)
references
References 28 publications
14
70
4
11
Order By: Relevance
“…Previous studies have found that obstruction and perforation tend to occur in the older age groups. 24,25 Our study was also in agreement with this observation.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found that obstruction and perforation tend to occur in the older age groups. 24,25 Our study was also in agreement with this observation.…”
Section: Discussionsupporting
confidence: 92%
“…Emergency colon surgery itself had a higher mortality rate than non-emergency colon surgery [2,[12][13][14]. The present study is of potential interest because sepsis is a very common problem in elderly patients who undergo emergency colorectal surgery.…”
Section: Discussionmentioning
confidence: 76%
“…[1][2][3]6 Emergency sur- gery for colorectal obstruction carries a higher morbidity than elective colon surgery and mortality of 10% to 28%. [1][2][3][4][5][6] This difference in outcome is related to the poor medical condition of the patients as well as to the unprepared bowel resulting in increased infectious complications. Effective measures that will allow for the delay of surgery until patients can be medically optimized and undergo mechanical preparation of the colon could result in improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The need for emergent surgery in a patient with an unprepared colon leads to significant morbidity and mortality. [1][2][3][4][5][6] In patients with advanced malignant disease or with prohibitive operative risk, surgical intervention for colorectal obstruction appears even less appealing. The need for a less morbid treatment modality has led to the use of self-expandable metallic stents (SEMS) to relieve colorectal obstruction.…”
Section: Introductionmentioning
confidence: 99%